Time Course of Exercise Training–Induced Muscle Strength Changes in Type 2 Diabetes. Issue 4 (October 2016) - Mathis, Ruth Ann; Taylor, J. David; Fletcher, James P.; Rainey, Jacquie; Cade, W. Todd; Bandy, William D.
Abstract : Purpose: To investigate longitudinal muscle strength changes in response to exercise training in people with type 2 diabetes. Methods: Twenty-one people with type 2 diabetes were randomly allocated to either a moderate or high-intensity exercise training group with the only difference between the groups being the prescribed exercise training intensity. Muscle strength (8 repetition maximum in kilograms) was measured weekly for 12 weeks using the chest press, leg press, row, and knee extension exercises. Muscle strength was expressed as the sum of 8 repetition maximum scores for each exercise. Results: Linear mixed models indicated significant gains in muscle strength ( P < .001) in both groups and no significant difference in gains in muscle strength ( P = .47) between the groups. Pooled data from both groups indicated significant improvement in muscle strength ( P < .05) week-to-week beginning after week 1 and continued until week 9. Conclusion: Participation in either a moderate or high-intensity exercise training program can result in similar gains in muscle strength for people with type 2 diabetes. Muscle strength improvements can occur on a weekly basis for the first 8 weeks of exercise training, with a plateau in gains occurring at week 9 through week 12.